Synthesis and Properties of Zinc Iron Phosphate Glasses Prepared by Microwave and Conventional Processing Methods - Mohd Farhadi, Nur Hazeeqah; Rosli, Rosziana; Kimpa, Mohammed Isah; Esa, Fahmiruddin; Ismail, Muhammad Hussain; Mayzan, Mohd Zul Hilmi (Journal of Science and Technology, 2017)
The synthesis and properties of zinc iron phosphate glasses, xZnO-(40-x)Fe2O3-60P2O5 where x = 0, 2.5, 5.0, 7.5, 10.0 (mol %) formed using domestic microwave oven and electric furnace are reported. In microwave glass melting, microwave absorber namely high purity magnetite powder has successfully coupled with microwave radiation at 2.45 GHz and completed the glass melting process at about 10 minutes radiation time. The properties of microwave samples are compared with equivalent samples prepared conventionally by melting the batches at 1300 ËšC for 2 hours in electric furnace. Although the mass loss trend is in agreement with the theoretical data, it is found that the microwave melted samples have slight increase in mass loss than conventionally melted ones and the mass loss is increased gradually with the increasing of ZnO contents. The powder density values of zinc iron phosphate glasses prepared using microwave method is found to be higher than the corresponding glasses prepared using conventional processing method. Identical trend of Fourier transform infrared spectra are recorded despite using different processing methods; it is clear that the addition of ZnO increased the cross-linking in the glass structure as well as improving the strength of the samples. Overall, the use of microwave radiation for the production of zinc iron phosphate glasses are promising and viable method as it gives comparable properties, faster glass melting and low energy consumption compared to conventional melting method.